Warmblood Fragile Foal Syndrome causative single nucleotide polymorphism frequency in Warmblood horses in Brazil - Dias, Natalia Moraes [UNESP]; de Andrade, Danilo Giorgi Abranches [UNESP]; Teixeira-Neto, Antônio Raphael; Trinque, Camila Moreira; Oliveira-Filho, José Paes de [UNESP]; Winand, Nena J.; Araújo, João Pessoa [UNESP]; Borges, Alexandre Secorun [UNESP] (Elsevier, 2019)
Warmblood Fragile Foal Syndrome (WFFS)is an autosomal recessive genetic disorder caused by a mutation in the procollagen-lysine, 2-oxoglutarate 5-dioxygenase 1 (PLOD1)gene, associated with collagen biosynthesis. WFFS causes lesions and malformations of the skin in neonatal foals, and abortion. The objective of this study was to investigate the allelic frequency of the single nucleotide polymorphism (SNP)c.2032G>A in the PLOD1 gene in warmblood samples from Brazil. Of the 374 Warmblood horses tested, 41 animals (11%)were identified as heterozygous for the WFFS SNP and 333 (89%)were homozygous for the wild-type allele (N/N), and therefore, the allele frequency was 5.5%. This study highlights the importance of control measures to prevent an increase in the incidence of WFFS in Warmblood horses worldwide.
Keywords: Collagen; Connective tissue; Mutation; PLOD1gene